Did the 2022 Hunga eruption impact the noctilucent cloud season in 2023/24 and 2024? - S. Wallis; M. DeLand; C. von Savigny (Atmospheric Chemistry and Physics)
The 2022 Hunga Tonga – Hunga Ha'apai eruption emitted approximately 150 Tg H2O into the middle atmosphere, which is still detectable 2 years after the event. Microwave Limb Sounder (MLS) observations show that the Hunga H2O reached the upper polar mesosphere in the Southern Hemisphere (SH) in the beginning of 2024, increasing the H2O mixing ratio in January by about 1 ppmv between 70 and 80° S up to an altitude of 83 km. No clear signal was detected for the noctilucent cloud occurrence frequency inferred from Ozone Mapping and Profiling Suite – Limb Profiler (OMPS-LP) measurements. It cannot, however, be ruled out that a slight increase from mid-January to February is potentially caused by the additional water vapour from the Hunga event. Several months later, the water vapour anomaly reached the polar summer mesopause region in the Northern Hemisphere (NH) during the noctilucent cloud season in 2024. However, a subsequent anomalous warming during the second half of the season might have hindered the ice particle formation, leading to a decrease in occurrence frequency of the mesospheric clouds compared to previous years. To summarize, based on the analysis performed in the study, we show that the volcanic water vapour needs 2 years to reach the summer polar mesopause region. This resembles the Krakatoa case that is argued to have caused the first sightings of noctilucent clouds 2 years after its eruption in 1883.